Care with allergen immunotherapy for allergic respiratory diseases in Germany—Predictors and deficits. Issue 12 (18th May 2022) - Valbert, Frederik; Neusser, Silke; Pfaar, Oliver; Klimek, Ludger; Sperl, Annette; Werfel, Thomas; Hamelmann, Eckard; Riederer, Cordula; Wobbe‐Ribinski, Stefanie; Hillerich, Vivienne; Neumann, Anja; Wasem, Jürgen; et al.
Abstract: Background: Allergen immunotherapy (AIT) represents the only possibility of causal therapy for allergic respiratory diseases. Although the prevailing high prevalence of allergic diseases and restrictions in the daily lives of patients, AIT is offered to a suboptimal number of patients in Germany. Methods: Insured patients with documented allergic respiratory disease of one of the largest statutory health insurances in Germany, 'DAK‐Gesundheit', were contacted by postal mail and asked to participate in the study. In case of written consent, primary and secondary data of patients were collected and analysed. Patient characteristics, predictors of being offered AIT, predictors of performing AIT and guideline‐compliant care were analysed. Results: 2505 subjects were included in the VerSITA study. Allergy to tree pollen and native speaking were identified as predictors, which increase the probability of being offered AIT. The probability was significantly decreased by the characteristics allergic rhinitis only, allergic asthma only, age in years, non‐German citizenship, no graduation and lower secondary qualification. Significant positive predictors for an AIT to be actually performed were: Allergy to tree pollen and male sex. Predictors that decrease the likelihood that AIT is performed were: only allergic asthma, current smoker, former smoker, age and non‐German citizenship. Furthermore, it was possible to identify characteristics in which guideline‐compliant patients differed significantly from the rest of the study population. Conclusions: Based on statutory health insurance data and patient survey data, the VerSITA study provides a broad and in‐depth overview of the care situation with regard to AIT in Germany and identifies deficits.